The Effect of Korean Brand Ambassador Towards Luxury Brand Purchase Intention (Journal of Business and Management, 2022)
Luxury brands will be really different for the next five year. They started to move from chasing American and European markets to rich millennials in Asia. Asia became the highest region that contributed for Dior revenue in 2020 with 34% and 8% for the Japan market only. Those numbers are very high and we can conclude that Asian market buying power for luxury brands is high. The phenomena of the Korean wave make luxury brands use the artist for their ambassadors, and also use the fanatic fans to increase their brand awareness. However it has not been tested if the strategy works for the luxury brand market penetration and increases the purchase intention. The objective of this research is to identify the factors that influence the purchase intention of a luxury brand by using Korean Brand ambassador and to understand the effect of Korean brand ambassador for luxury brands on purchase intention in Indonesia. In this study research used quantitative methods by collecting data through survey questionnaires and judgmental sampling as the sampling method with the total of 148 respondents that are luxury brand consumers, also using PLS-SEM to analyze the result of the survey. The result shows that celebrity endorsement positively impacted luxury brand purchase intention through brand trust, brand psychological ownership, and brand attitude.